2018
DOI: 10.1037/str0000058
|View full text |Cite
|
Sign up to set email alerts
|

Coaching as stress-management intervention: The mediating role of self-efficacy in a framework of self-management and coping.

Abstract: This study aims at expanding the evidence-base of coaching and explores how coaching contributes to coping. It offers a model for coaching as an intervention affecting an individual’s stress management, which, in essence, explores one psychological “mechanism” of coaching-facilitated change by relating self-management with coping and taking into account self-efficacy as a mediator. We hypothesize that coaching alters clients’ self-management skills and self-efficacy beliefs, and further, in light of previous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 144 publications
(178 reference statements)
0
7
0
1
Order By: Relevance
“…Self-efficacy has been found to be central at various levels of a system such as, for instance, a school, a family, or an individual (e.g., Bandura et al, 1999 ; You et al, 2016 ; Höltge et al, 2019 ). Indeed, it was shown to be positively associated not only with performance related constructs like coping behavior, problem solving, and academic performance (e.g., Caprara et al, 2008 ; Ebner et al, 2018 ; Li et al, 2018 ), but also with indicators of mental health such as lower anxiety and depression, as well as higher life satisfaction (e.g., Bandura et al, 1999 ; Tahmassian and Moghadam, 2011 ; Moksnes et al, 2018 ). Results from large-scale studies on resilience showed that self-efficacy is positively associated with resilience ( Werner, 1996 ; Masten et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy has been found to be central at various levels of a system such as, for instance, a school, a family, or an individual (e.g., Bandura et al, 1999 ; You et al, 2016 ; Höltge et al, 2019 ). Indeed, it was shown to be positively associated not only with performance related constructs like coping behavior, problem solving, and academic performance (e.g., Caprara et al, 2008 ; Ebner et al, 2018 ; Li et al, 2018 ), but also with indicators of mental health such as lower anxiety and depression, as well as higher life satisfaction (e.g., Bandura et al, 1999 ; Tahmassian and Moghadam, 2011 ; Moksnes et al, 2018 ). Results from large-scale studies on resilience showed that self-efficacy is positively associated with resilience ( Werner, 1996 ; Masten et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we discovered that self-efficiency strengthens the link between empowering leadership and job performance. Hence, top management can improve the employees' self-efficacy and goal clarity by giving them a role, training, coaching, and enlarging their jobs (Ebner et al, 2018). Secondly, goal clarity has a statistically significant and positive association with empowering leadership and job performance (Harris, Li, Boswell, Zhang, & Xie, 2014).…”
Section: Practical Contributionmentioning
confidence: 99%
“…Nach der sozial-kognitiven Theorie von Bandura (1997) gilt die Selbstwirksamkeitserwartung als ein Schlüsselfaktor für das menschliche Handeln. Verschiedene Studien weisen darauf hin, dass die Selbstwirksamkeitserwartung für das Wohlbefinden, die psychische Gesundheit und für akademische Leistungen zentral ist (Bandura, Pastorelli, Barbaranelli & Caprara, 1999;Caprara, Barbaranelli, Pastorelli & Cervone, 2004;Ebner, Schulte, Soucek & Kauffeld, 2018;Graber, Turner & Madill, 2016;McCauley, Weymouth, Feinberg & Fosco, 2019).…”
Section: Erziehungsbezogene Elterliche Depressivität Und Selbstwirksamkeitserwartung Von Kindern: Die Rolle Von Freundschaftsqualitätunclassified